The Embodied Self-Representations of Older Women: A Qualitative Study Protocol for Developing and Evaluating a Therapeutic Model with Narrative and Phototherapy Techniques - Silvia Piol; Hod Orkibi; Shoshi Keisari (International Journal of Qualitative Methods)
Gendered ageism, the intersection of ageism and gender bias, conceptualizes how social constructions shape attitudes toward older women and restrict their access to societal resources. As oppressive gendered ageist stereotypes can affect how older women perceive their embodied selves, interventions tailored to women’s needs are essential to maintaining a positive identity. This research protocol aims to develop an arts-based intervention specifically adapted to the psychosocial needs of community-dwelling older Italian women. It centers on the embodied self-representations of older women from a life-course perspective that integrates narrative and phototherapy techniques. In the first phase of this research project, a pragmatic approach will be taken to explore professionals’ use of phototherapy techniques with aging women; the data will be analyzed through reflexive thematic analysis. Building on the findings and the literature, an intervention will then be developed for older women. In the second phase, a narrative approach will be taken to probe the embodied self-representations of older Italian women as expressed in their narratives and photographic art products; the data will be analyzed through polytextual analysis of personal narratives. In the third phase, interviews based on the arts-based approach and the Client Change Interview will be conducted with older women to examine the psychosocial contribution of the intervention and their experiences with the artistic process and products; the data will be analyzed through reflexive thematic analysis. To uphold qualitative research rigor, data triangulation, reflexive journaling, auditing, and member checking will be employed. The data collection will be conducted between 2024 and 2025. The findings of this study will shed light on the embodied self-representations of older women in Italy as they emerge in their narratives and phototherapy artworks and will provide an empirically based intervention that integrates narrative and phototherapy techniques tailored to their psychosocial needs.